WIDOWHOOD IN MANCHEGA RURAL SOCIETY. MARRIAGE AND SOCIAL REPRODUCTION STRATEGIES AT THE END OF THE ANCIENT REGIME - Simón García, Maria (Revista de Historia Social y de las Mentalidades, 2025)
This article tries to enter itself in the social fr amework of the population through the widowhood, not only like a demographic accident, bu t like a life form, an identity, a social construction. For the social study of the widowhood the crossing of diverse types of documentary sources will be necessary. In this meth odology the parochial, notarial and cadastral registries acquire a transcendental importance in t he analysis of the vital cycle of the widowers and widows. Age, gender, descendants or patrimony w ill be the pillars around which it turns this proposal of study. One is to catch behaviors and so cial processes of mobility and social reproduction. Moveove we will try to explain not on ly relationships concerning family, kinship and dependency, but also solidarity and reciprocity . The married alliance becomes the best channel of patrimony in which kinship, consanguinit y and affinity are tools of analysis of the remarriage. For social groups the marriage was a si gnal agent of the property, where patrimony, marriage and inheritance acted like mechanisms of s ocial mobility and reproduction of the system constituted in the hierarchial structuring a nd the inequality. Nevertheless other more underprivileged groups considered the alliance marr ied as a vital strategy of survival.